Nutritional Composition of Cassava Cultivar "CARI-555" - Somendrika, M.A.D.; Wickramasinghe, l.; Wansapala, M.A.J.; Peiris, S. (Pakistan Journal of Nutrition, 2017)
Background: Humid tropical root crop cassava (Manihot esculenta) is one of the most important metabolic sources of calories. The root, which consists of outer phelloderm (peel), parenchyma (starchy bulk of the root) and central vascular core is the main commercial product of cassava. Objective: The present study was conducted to analyze the proximate composition (moisture, ash, total fat, crude fibre, protein and carbohydrate) in the peel and the flesh of cassava cultivar "CARI-555". Materials and Methods: The proximate composition (moisture, ash, crude fibre, crude protein and total fat) of the six samples was determined using standard methods with three replicates. The carbohydrate content was calculated by the difference. Results: The moisture, ash, fat, crude protein, crude fibre and carbohydrates amounts of the flesh sample were 52.70±0.52, 0.87±0.06, 1.87±0.68, 0.91±0.16, 0.91±0.02 and 42.74±0.46%, respectively. The moisture, ash, fat, crude protein, crude fibre and carbohydrates amounts of the phelloderm (peel) sample were 58.88±0.25, 1.00±0.05, 1.34±0.18, 1.23±0.08, 1.72±0.03 and 35.83±0.22%, respectively. A negative correlation was significantly exist (p